Effects of physical fitness, parenting style, and secondhand smoke exposure predict physical education learning outcomes - Alfi Mukhti; Padli Padli; Rika Sepriani; Fahd Mukhtarsyaf; Firunika Intan Cahyani (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study aimed to investigate the effects of physical fitness, parenting style, and secondhand smoke exposure on Physical Education learning outcomes and to examine the mediating role of secondhand smoke exposure. A quantitative correlational design was employed involving 38 fifth- and sixth-grade students from Kuranji Elementary School Number 32nd, Padang City, selected through total sampling. Data were collected using the Indonesian Student Fitness Test (TKSI), parenting style and secondhand smoke exposure questionnaires, and Physical Education academic records. Data were analyzed using path analysis with IBM SPSS Statistics 27. Physical fitness had a positive and significant effect on Physical Education learning outcomes (β = 0.427; p < 0.001), while parenting style (β = −0.379; p = 0.001) and secondhand smoke exposure (β = −0.344; p = 0.001) also showed significant effects. The model explained 68.2% of the variance in Physical Education learning outcomes. Physical Education learning outcomes are influenced not only by students' physical fitness but also by family environmental factors, particularly parenting practices and reduced exposure to secondhand smoke.